(untitled) (Tempo e Argumento, 2012)
This paper analyzes the book Heading South, Looking North(1998), written by the American intellectual Ariel Dorfman. Considering the reading of his memoirs, it attempts to understand how the author, based on his life as well as his family’s, has constructed the bilingualism that has characterized his trajectory. Through the constitution of his multiple, but not always excluding identities, Dorfman has pointed out reasons for the approximation between a man linked to left-wing projects in Latin America and North-American cultural references, by means of migrations that have always been present in his life.